Analyzing the Errors Made by Advanced Student on (Subject-Verb) Concord at Misan University - Emad Jasem Mohamed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
In grammar, concord is a broad notion that applies primarily to two lexical groups - the nominal group (nouns and pronouns) and the verbal group. thus talking of subject-verb concord and pronoun-antecedent concord. Subsumed under the subject-verb concord is the “notional concord” and “proximity concord". Concord means agreement. In English grammar, it is the agreement in number and person between a verb and its subject, and in number, person and gender and case between a pronoun with its antecedent. This study concerns subject-verb concord only, regardless of another grammatical concord like subject-object concord or subject–determiner concord. The aims of this study are to investigate the main problems faced by advanced students in subject-verb concord and to reduce the grammatical errors made by students in the area of subject-verb concord by enriching their grammatical knowledge concerning subject-verb concord.The researcher selected 66 Iraqi EFL third-year students as a sample for the study and constructed a test comprising (20) items in order to achieve the study's objectives. The exam consists of multiple-choice questions. The exam is used to assess a student's understanding of subject-verb concord. The findings of this study indicate that during the delivery of the exam, there is a variation in the production of the groups (pretest and posttest).DOI /10.54633/2333-021-042-034